The science book explore and learn the big ideas of science - DK Publishing, Inc (London DK Publishing, 2015)
The Science Book is an inventive visual take on astronomy, biology, chemistry, geology, and physics. With eye-catching artwork, step-by-step diagrams, and illustrations that break down complicated ideas into manageable concepts, The Science Book will have readers conversant in genetic engineering, black holes, and global warming in no time. Along the way are found mini-biographies of the most well-known scientists, and a glossary of helpful scientific terms
Science
1
Keywords: Science -- Juvenile literature; Science -- Popular works -- Juvenile literature